Grounding Translation and Interpreting in the Brain: What Has Been, Can Be, and Must Be Done - Muñoz-Arias, E (Taylor and Francis Ltd., 2019)
This paper offers an overview of neurocognitive research on translation and interpreting, an area whose history spans almost 100 years. First, we identify the main milestones in the development of this field, considering empirical breakthroughs (based on neuropsychological and neuroscientific evidence) as well as theoretical and institutional advances. Second, we review three areas of inquiry for which abundant evidence is already available, namely: (i) the circuits involved in backward and forward translation, (ii) the mechanisms engaged depending on variables of the translation unit, and (iii) the neurocognitive impact of expertise in simultaneous interpreting. Third, we discuss the field’s prospects for development, identifying key possibilities and methodological limitations. Finally, we enumerate the principal requirements for the consolidation of the neurocognitive approach (e.g. interdisciplinary training, greater collaboration between translation studies scholars and neuroscientists, increased funding, and presence in high-impact journals). In sum, we intend to show that knowledge about the cerebral basis of translation and interpreting has been growing over the decades and that conditions are appropriate for this promising space to assert itself as a full-fledged research arena. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.